An Innovative Water Reaction Turbine of the Ultra Z-Blade Designed for Water Conditions of Low-Head and Ultra-Low Flow - Nurul Ashikin Mohd Rais; Mohd Farriz Basar; Mohd Ikram Mohd Nor Rizan (International Journal of Integrated Engineering, 2025)
In comparison to conventional fossil fuels like coal and gas, hydropower offers many advantages. This is because it does not discharge harmful gases into the atmosphere, which contributes to air pollution. Nevertheless, there will be negative ecological effects in the area around a hydropower energy-producing plant if it is built. Hydropower is significantly less dangerous than pico-hydro systems, which only require a trickle of water to generate electricity through the rotation of a turbine. The reaction-type turbine is the topic of this study because it can be rotated by a relatively small amount of water. Cross pipe turbines (CPTs), split reaction turbines (SRTs), and Z-blade turbines (ZBTs) are all examples of older turbine designs that prioritized pressure above flow. There has been little progress made so far to compensate for the low head and ultra-low flow water segment. In order to tap into low head and ultra-flow water resources, this work attempts to address this by developing an ultra z-blade turbine for pico-hydro producing systems with two types of pipes measuring 0.75 inches and 2.0 inches in diameter. The concepts of mass, momentum, and energy conservation are used to generate the equations. The performance of the newly developed U-ZBT is compared to that of the well-established CPT, SRT, and ZBT via an experimental method. As a result, a 0.75-inch pipe size performed better than a 2.0-inch pipe size at a maximum speed of 130 rpm and a water flow rate of 1.77 L/sec.